Basra Between Sasanian Influence and Arab MovementsA Historical Reading in the Dialectic of Conflict and Coexistence - Abdul Ali Hamid Al-Mayah , Lect . Dr. Anwar (Basra studies journal, 2026)
This Research examines Basra during the Sasanian period as a zone of cultural and political interaction between the Sasanian Empire and the Arab tribes. The Sasanians relied on garrisons and frontier outposts to secure their dominance over Al-Ubulla and the Shatt al-Arab, yet their control remained fragile due to persistent Arab raids and shifting alliances based on mutual interests. At the same time, the Arabs were not merely a rebellious force; they also engaged in trade and social exchange, creating a state of forced coexistence. The study demonstrates that the relationship between the Sasanians and the Arabs was a complex dialectic of conflict and coexistence, which gradually weakened Sasanian authority, fostered a sense of Arab independence, and paved the way for the Muslim conquest. Thus, Islamic Basra did not emerge in isolation but represented a continuation and qualitative transformation of a cumulative legacy of both conflict and coexistence.